Exploring health behaviors and the role of pet dogs in households with autistic children: the DANE study - Adkins, Janna R.; Mulé, Christina M.; Linder, Deborah E.; Must, Aviva; Cash, Sean B.; Folta, Sara C. (Frontiers in Pediatrics, 2023)
INTRODUCTION. Autism spectrum disorder (ASD) often presents a unique set of risk factors that impact healthy eating and physical activity. Animal-assisted interventions (AAI) are a promising approach for autistic children. There is growing evidence for the positive impact of AAIs on self-regulation, which is necessary for initiating and maintaining behavioral changes. Pet dogs offer several potential advantages as a vehicle for an AAI focused on health behaviors. However, little is known about the experiences of autistic children and their families with respect to dog ownership and the mechanisms through which such an AAI might operate. METHODS. We conducted interviews with ten parent-child dyads to explore the role of pet dogs in the lives and lifestyle habits of families with an autistic child. Interview guides were designed to explore the relationship between the autistic child and the pet dog and the role of the dog in family life; attitudes and practices related to physical activity and nutrition; and thoughts about intervention strategies. We used a directed qualitative content analysis approach for analysis. RESULTS. Themes indicate a strong bond between the child and the dog, the child’s enjoyment in caring for their dog, and successful integration of dogs within family routines. In contrast, minor themes emerged around the challenges that owning a pet dog posed for families with an autistic child. In terms of nutrition and physical activity, a major theme among children was that healthy eating and exercise were important for both them and their dogs. However, minor themes suggest challenges with healthy eating and exercise and room for improvement for these behaviors. Parents held favorable views toward an intervention that would incorporate the family dog to teach children about nutrition and physical activity, although they expressed some concerns about feasibility. DISCUSSION. This exploratory work suggests that AAIs to improve nutrition and physical activity could build on the strong bond that children have with their pet dogs, but should consider the specific needs of each family, including the needs of the pet dog.